2010
DOI: 10.1175/2009jcli2685.1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Precipitation Return Values in Complex Terrain and Their Evaluation

Abstract: To determine return values at various return periods for extreme daily precipitation events over complex orography, an appropriate threshold value and distribution function are required. The return values are calculated using the peak-over-threshold approach in which only a reduced sample of precipitation events exceeding a predefined threshold is analyzed. To fit the distribution function to the sample, the L-moment method is used. It is found that the deviation between the fitted return values and the plotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
(34 reference statements)
2
29
0
Order By: Relevance
“…The value of RCMs depends on the physical parameterizations, experimental setup, the analyzed variable and location (Feser et al, 2011). Although a large number of studies have validated the RCM output and have demonstrated that RCMs can realistically simulate climate compared to observations (e.g., Früh et al, 2010), mostly they have not explicitly shown whether the capabilities of the RCM exceed those of global forcing data (Prömmel et al, 2010).…”
Section: K Klehmet Et Al: a Regional Climate Model Hindcast For Sibmentioning
confidence: 99%
“…The value of RCMs depends on the physical parameterizations, experimental setup, the analyzed variable and location (Feser et al, 2011). Although a large number of studies have validated the RCM output and have demonstrated that RCMs can realistically simulate climate compared to observations (e.g., Früh et al, 2010), mostly they have not explicitly shown whether the capabilities of the RCM exceed those of global forcing data (Prömmel et al, 2010).…”
Section: K Klehmet Et Al: a Regional Climate Model Hindcast For Sibmentioning
confidence: 99%
“…Hagemann et al 2009, Endler & Matzarakis 2010, Früh et al 2010, Kjellström et al 2011). According to the study by Reichler & Kim (2008), EH5OM is one of the most successful CMIP3 1 global models in simulating the climate of the 20th century.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are numerous applications of the POT approach which do not consider timedependent parameters (e.g. Madsen et al, 1997;Claps and Laio, 2003;Bacova-Mitkova and Onderka, 2010;Fruh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%